Characteristics of books that bring on a higher probability of being lost - Dizon, Heidi Kalayaan M. (2001)
The purpose of this study was to determine the distinct qualities of books that bring on a higher probability of being lost. It also aimed to identify the possible preventive measures in minimizing if not eliminating the probability of books getting lost. Specifically, this study tried to answer the questions ""What are the characteristic of books that bring on a higher probability of being lost?"", ""In what subject area/-s does the book belong?"", ""When was it published?"", ""What is the size of the book?"". ""Is it thick or thin?"", ""Is it illustrated or not?"", ""Is it rare?"", ""Where was the book published?""